Effects of straw mulching on dry matter distribution and grain yield of summer maize - C.J. Ma; C.Y. Bian; X.H Liu; Z.X Yan; C. Gao; Y.J. Ren; Q.R Liu; Q.Q. Li; H.F. Han2 (Journal of Animal and Plant Sciences, 2017)
The limited land resources are compelling the farming community to implement high-yielding measures. Straw mulching is an effective way to sustain soil fertility and increase summer maize grain yield. To evaluate the effect of straw mulching on summer maize productivity, field experiments were conducted during 2010 and 2011 at Experimental Station of Shandong Agricultural University. The experiment adopted a split plot design arranged in randomized blocks with three replications. Main plots were plant type, including compact type, Chaoshi1 (C), and flat type, Danyu86 (D); subplots consisted of straw mulching amount: 0, 0.6, and 1.2 kg/m2, treatments consists of C0, C0.6, C1.2; D0, D0.6 and D1.2. The results indicated that straw mulching increased LAI at the earlier growing stage but decreased LAI at the later growing stage; there was a significant effect on PAR capture ratio for Danyu6 but not in Chaoshi1, the capture ratio was significantly higher in D0.6 and D1.2 than D0, and the increasing the proportion were by 8.3% and 11.0%, respectively. Straw mulching increased both cob dry matter and stems and leaves dry matter in Danyu86; however, straw mulching increased cob dry matter and decreased stems and leaves dry matter in Chaoshi1. Results support the application of straw mulching in combination with plant types for maximizing summer maize grain yield in the North China Plain.
Keywords: straw mulching; leaf area index; PAR capture ratio; yield compositions; summer maize